LOKASI SUMBERDAYA MANUSIA DI JEPANG - Prasetyo Soepono (Journal of Indonesian Economy and Business (JIEB), 1999)
It is said that migration in any advanced counties like Japan has been insignificant since income levels in provinces of Japan has reached convergence. But Statistics Bureau of Japan published data on inter-province migration for 1990 and on the basis of tlisese data , it is found that migration in Japan was stili meaningful from which developing countries like Indonesia can learning something in distributing its re oun.e especially human resources. Three research qustions are raised: (I) which migration law prevailed in 1990? (2) since the 1990 migration data shows high in-migration and high out-migration, what factors affected in-migration in Japan in 1990? And (3) what factors affected out-migration? The first finding shows that like in any other advanced countries, high in-migration is highly correlated with out-migration, which means that the Lowry hypothesis has been accepted or the second law of migration prevailed in Japan. The second finding shows that income per capita, urbanization, density and temperature had positive and significant impact on in-migration in 1990. The third and last finding reveals that education had positive and significant impact on out-migration, whereas age had negative and significant influence on out-migration. Hie identification of the determinants of in-migration and those of out-migration and the accurate estimation of the in-migration model and of the out-migration model can he the useful basis for formulating regional development strategy like the one adopted by Japan (under the term "age of provinces") for any country